2019
DOI: 10.5435/jaaos-d-17-00868
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Questions Asked of Female Orthopaedic Surgery Applicants From 1971 to 2015: A Cross-sectional Study

Abstract: Introduction:The Civil Rights Act prohibits employers from making employment decisions based on sex, race, color, religion, or national origin. Questions regarding these topics during a residency interview are therefore prohibited. Methods: A questionnaire was sent to all female orthopaedic surgeons who had an e-mail address in the American Academy of Orthopaedic Surgeons directory. Participants were asked to describe what, if any, inappropriate questions they were asked during interviews.Results: Four hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…In total, 13 papers50–62 concentrated on gender discrimination during the process of residency application, including recommendation letters51–55 and interview,56–60 and fellowship applications 61,62. In standardized letters of recommendation most of these differences seem to disappear 52.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 13 papers50–62 concentrated on gender discrimination during the process of residency application, including recommendation letters51–55 and interview,56–60 and fellowship applications 61,62. In standardized letters of recommendation most of these differences seem to disappear 52.…”
Section: Resultsmentioning
confidence: 99%
“…The main reasons for not reporting harassment have been found to be "fear of negative impact on my career" (43%), "fear of retribution" (32%) and "fear of being dismissed and inaction towards perpetrator" (31%), 49 "feeling that nothing would come of it if reported" (44%), "not being aware about institutional mechanisms to report harassment" (34%). 47 In total, 13 papers 50-62 concentrated on gender discrimination during the process of residency application, including recommendation letters [51][52][53][54][55] and interview, [56][57][58][59][60] and fellowship applications. 61,62 In standardized letters of recommendation most of these differences seem to disappear.…”
Section: Surgical Trainingmentioning
confidence: 99%
“…Samora et al 19 found that 81% of female respondents of an AAOS survey had experienced discrimination, bullying, or harassment. Similarly, in a Ruth Jackson Orthopaedic Society survey, 68% of women reported having experienced sexual harassment during their orthopaedic training, and 61.7% reported being asked an inappropriate question during residency interviews, including issues about child-bearing and marital status 20 , 21 . In a survey of women in orthopaedics, 74% had experienced microaggressions, which are defined as verbal, nonverbal, or environmental slights that are either intentional or unintentional conveying hostile, derogatory, or otherwise negative messages 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of women orthopedic surgeons, 61.7% were asked inappropriate questions about pregnancy and child-rearing during residency interviews. 5 This alarming percentage did not vary from 1971 to 2015. Furthermore, unstructured interviews have low interrater reliability and poor prediction of on-the-job performance.…”
mentioning
confidence: 92%
“…Nevertheless, discrimination in hiring has not changed, perhaps because applicants rarely report discriminatory or inappropriate hiring practices. 5 Although antidiscrimination laws theoretically protect applicants, fair hiring practices are usually the result of employers' commitment to uphold these laws. Cardiothoracic programs must critically review recruitment practices to ensure compliance with antidiscrimination laws and promotion of diversity.…”
mentioning
confidence: 99%